The Relationship Between Body Mass Index (BMI) and Blood Pressure in Hypertensive Patients at Ciptodadi Community Health Center, Musi Rawas Regency, and Its Review from an Islamic Perspective - Keisa Yude Prameswari; Diniwati Mukhtar; Muhammad Arsyad (CV. Publikasi Indonesia, 2025)
This study examines the relationship between Body Mass Index (BMI) and blood pressure (hypertension) in the Ciptodadi Community Health Center, Musi Rawas Regency. Hypertension, a non-communicable disease, is influenced by factors like BMI, with higher BMI contributing to increased blood pressure. An observational analytical study with a cross-control approach involved 60 respondents, 30 with hypertension and 30 without. Blood pressure and BMI were measured, and data were analyzed using the Chi-Square test. The results indicated a significant relationship between BMI and blood pressure, with 40% of respondents with a BMI ≥23 kg/m² having hypertension, compared to 16.7% without hypertension. The Chi-Square test yielded a p-value of 0.00, with an odds ratio (OR) of 8.000, suggesting a significant association between BMI and hypertension. The study concludes that individuals with excess BMI are at a higher risk of developing hypertension. From an Islamic perspective, maintaining BMI and blood pressure aligns with the obligation of hifz an-nafs (preserving the soul).